Cannabinoid-Based Ocular Therapies and Formulations - Sofia M. Saraiva; Lucía Martín-Banderas; Matilde Durán-Lobato (MDPI AG, 2023)
The interest in the pharmacological applications of cannabinoids is largely increasing in a wide range of medical areas. Recently, research on its potential role in eye conditions, many of which are chronic and/or disabling and in need of new alternative treatments, has intensified. However, due to cannabinoids' unfavorable physicochemical properties and adverse systemic effects, along with ocular biological barriers to local drug administration, drug delivery systems are needed. Hence, this review focused on the following: (i) identifying eye disease conditions potentially subject to treatment with cannabinoids and their pharmacological role, with emphasis on glaucoma, uveitis, diabetic retinopathy, keratitis and the prevention of Pseudomonas aeruginosa infections; (ii) reviewing the physicochemical properties of formulations that must be controlled and/or optimized for successful ocular administration; (iii) analyzing works evaluating cannabinoid-based formulations for ocular administration, with emphasis on results and limitations; and (iv) identifying alternative cannabinoid-based formulations that could potentially be useful for ocular administration strategies. Finally, an overview of the current advances and limitations in the field, the technological challenges to overcome and the prospective further developments, is provided.